Pengaruh Pelatihan Apoteker Terhadap Pengetahuan Dan Keterampilan Dalam Penanganan Kasus Farmasi - Dahniar Dahniar (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Pharmacists play a crucial role in pharmaceutical services, particularly in ensuring the safe, effective, and rational use of medications. Improving pharmacist competency through ongoing professional training is essential to enhance knowledge and skills in pharmaceutical case management. This study aimed to analyze the effect of pharmacist training on improving knowledge and skills in pharmaceutical case management. The study used a quasi-experimental design with a pretest–posttest approach. A sample of 35 pharmacists working in healthcare facilities was selected using a purposive sampling technique. Knowledge was measured using a multiple-choice questionnaire, while skills were assessed through a pharmaceutical case study simulation. Data were analyzed using a paired t-test. The results showed a significant increase in knowledge scores from 62.4 ± 9.3 to 81.7 ± 7.6 and in skills scores from 65.2 ± 8.7 to 83.5 ± 6.9 (p < 0.001). It was concluded that pharmacist training effectively improves competency in pharmaceutical case management.